Long-term cognitive and autonomic effects of COVID-19 in young adults: a cross-sectional study at 28 months - Gopika Gopinath; Chinmay A. Suryavanshi; Pallavi L. C. (Annals of Medicine)
Objectives The COVID-19 pandemic, caused by SARS-CoV-2, has had profound global impacts since its emergence in late 2019. Whilst acute symptoms are well-documented, increasing evidence suggests long-term consequences extending beyond the acute phase. This study aimed to investigate the long-term cognitive and autonomic effects of COVID-19 in young adults.Materials and Methods We conducted a cross-sectional study comparing young adults with a history of COVID-19 (n = 34) to matched controls (n = 34). Cognitive function was assessed using the Sternberg Task, Stroop Task, and Go/No-Go Task (GNG). Autonomic function was evaluated using heart rate variability (HRV) parameters.Results The average time interval between COVID-19 infection and testing was 28.2 months. The COVID-19 group showed significantly increased reaction time in the 2-item absent condition (p = 0.044) and errors in the 4-item present condition (p = 0.012) of the Sternberg Task and increased neutral response time (p = 0.028) and the normalized time for completing the task (p = 0.022) in the Stroop Task. No significant differences were found in the GNG Task. HRV parameters did not differ significantly between groups, although trends toward higher overall HRV were observed in the COVID-19 group.Conclusion Young adults who had COVID-19 infection approximately 28 months ago show minimal long-term impact on cognitive function and autonomic regulation. However, subtle cognitive inefficiencies persist, particularly in working memory and executive function tasks. These findings suggest a generally favorable long-term prognosis for young adults following mild to moderate COVID-19 but highlight the need for further investigation into persistent subtle cognitive effects and autonomic effects.